Experimental and numerical simulation study on the flow characteristics and optimization of structural parameters of displacement agent in partial pressure tools. Issue 4 (18th December 2019) - Huang, Bin; Hu, Xinyu; Fu, Cheng; Cheng, Haoran; Li, Yuehua
Abstract: In order to solve the problem of reservoir heterogeneity in the process of oil displacement, Daqing oilfield has proposed a partial pressure injection technology (using partial pressure tools). The partial pressure tool can improve the overall oil displacement effect by reducing the pressure of the displacement agent and adjusting the injection amount of the displacement agent in the high‐permeability oil layer. In order to study the effect of the partial pressure tool on the polymer solution, the flow characteristics of the polymer solution in the partial pressure tool were studied by finite element analysis, and the results of the numerical simulation were compared and verified by laboratory experiments. Then, the optimal structural parameters of the partial pressure tool were selected by orthogonal experiments. Finally, field tests were carried out to verify the effectiveness of the partial pressure tool. The results show that when the flow rate is 10 m 3 /d, the pressure drop of the polymer solution reaches 6.08 × 10 5  Pa and the viscosity loss rate reaches 6.69%, while the physical parameters of the solution change periodically under the action of the partial pressure tool. At a low flow rate, the results of the laboratory experiment and numerical simulation fit well, and the optimal structural parameters of the partial pressure tool are selected. Field tests show that the oil recovery is increased by 2.54% after using partial pressure tools. The research results are of great significance to the study of resolving interlayer conflicts and enhancing oil recovery. Abstract : The recovery ratio is increased after using partial pressure tools.